SIMILARITIES AND DIFFERENCES OF VERBS IN ENGLISH AND UZBEK LANGUAGES. (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Annotation: Verbs are one of the most important parts of speech in both English and Uzbek. They are used to describe actions, states, or occurrences, and they can be conjugated to indicate the tense, aspect, mood, and person of the action or occurrence.English and Uzbek verbs have many similarities, but there are also some key differences. These differences can be attributed to the different historical development of the two languages.